An acoustical investigation of Danish intonation: preliminary results - Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1976)
The relationship between linguistic stress and fundamental frequency in short declarative sentences and the intonation contours of short declarative sentences, interrogative sentences, and non-terminal clauses in Advanced Standard Copenhagen Danish are investigated. A tentative model for Fo patterns and -contours in such short simple (i.e. non-compound) sentences is proposed. The model predicts the following (which is to a large extent confirmed by the data): A stressed syllable and all succeeding unstressed syllables within the same simple sentence constitute a stress group, irrespective of intervening morphological and syntactical boundaries. Sentence initial unstressed syllables constitute a separate entity and are lower than the first stressed syllable which is always relatively high. A stressed syllable is lower than the immediately succeeding unstressed syllable (in the same stress group). The unstressed syllables in the stress group describe a falling Fo course. The more unstressed syllables there are, the more likely the last ones are to be lower than the stressed syllable in the succeeding stress group. The stressed syllables describe a falling contour in declarative sentences and an almost level one in interrogative sentences where the only cue distinguishing the interrogative from the declarative sentence is the intonation. The rest of the interrogative sentences and the non-terminal clauses are situated between these two extremes.